2018
DOI: 10.20886/jpth.2018.12.1.25-39
|View full text |Cite
|
Sign up to set email alerts
|

INTERAKSI FAMILI × LOKASI PADA UJI KETURUNAN GENERASI KEDUA Eucalyptus pellita

Abstract: The interaction assessment of genotype and environment is necessary to find out an effective selection strategy in progeny trial, particularly in advanced generations. This study aims to observe the effect of family × site interaction in second generation progeny trial of Eucalyptus pellita planted at two locations: Wonogiri, Central Java and Pelaihari, South Kalimantan. The trials design were completely randomized block design (CRBD) with 49 families, 6-10 blocks, 5 tree-plot and 4 m × 1.5 m spacing. Data mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The stand volume for E. pellita after 36 months in this study was lower than the study in South Sumatra reported by Hardiyanto et al [12] with approximately 75 m 3 .ha -1 . It shows that the appropriate site planting conditions are crucial for the growth of E. pellita [10]. The rainfall in South Sumatra was reported >2500 mm.yr -1 , while the rainfall in Wonogiri, Central Java was around 1600 mm.yr -1 .…”
Section: Stand Productivity and Energy Potentialmentioning
confidence: 97%
See 1 more Smart Citation
“…The stand volume for E. pellita after 36 months in this study was lower than the study in South Sumatra reported by Hardiyanto et al [12] with approximately 75 m 3 .ha -1 . It shows that the appropriate site planting conditions are crucial for the growth of E. pellita [10]. The rainfall in South Sumatra was reported >2500 mm.yr -1 , while the rainfall in Wonogiri, Central Java was around 1600 mm.yr -1 .…”
Section: Stand Productivity and Energy Potentialmentioning
confidence: 97%
“…The Acacias species is more tolerance in such unfavourable site conditions [9]. While the E. pellita often requires a site with well-fertilized soil and high rainfall (>2500 mm) [10]. The E. pellita and Acacia hybrid had slightly distinct growth patterns.…”
Section: Stand Productivity and Energy Potentialmentioning
confidence: 99%